视黄醇对人脐带间充质干细胞表皮生长因子、干细胞因子、集落刺激因子1和白血病抑制因子的影响 (Nan Fang Yi Ke Da Xue Xue Bao, 2017)
OBJECTIVE: To investigate effects of retinol on the expressions of epidermal growth factor (EGF), stem cell factor (SCF), colony-stimulating factor 1 (CSF1) and leukemia inhibitory factor (LIF) in cultured human umbilical-derived mesenchymal stem cells (UCMSCs). METHODS: Human UCMSCs were isolated from human umbilical cord and identified for immunophenotypes. The cells were then cultured in DMEM/F12 media supplemented with 12% fetal bovine serum (FBS), 12% FBS + 1 μmol/L retinol, 15% knockout serum replacement (KSR) and 15% KSR + 1 μmol/L retinol. The expressions of the cytokines EGF, SCF, CSF1 and LIF in the cells were detected using RT-PCR and ELISA. RESULTS: The isolated cells exhibited characteristic immunophenotypes of human UCMSCs and expressed EGF, CSF1 and SCF at both mRNA and protein levels but not LIF protein. Retinol (1 μmol/L) significantly promoted the expressions of SCF and CSF1 at both mRNA and protein levels but did not result in changes of EGF and LIF expressions in human UCMSCs. CONCLUSION: Retinol at the concentration of 1 μmol/L can promote expression of SCF and CSF1 in human UCMSCs in vitro.